Common Ground Nine-Level Boost Inverter for Grid-Connected PV Applications - Gopinath, Narayanan Pandurangan; Vijayakumar, Krishnasamy (Frontiers in Energy Research, 2022)
The article discusses a nine-level switching capacitor-based common ground-type boost inverter for grid-connected photovoltaic applications. The proposed structure’s direct connection between the negative terminal of the input source and the grid neutral eliminates leakage current. The proposed topology uses eleven switches, two diodes, and three switching capacitors to produce a double voltage boost with nine different voltage levels. Self-balancing switching capacitors eliminate the need for sophisticated independent control algorithms. The maximum voltage stress on one of the three capacitors equals the input voltage, while it is equal to half of the input voltage on the other two switched capacitors. The various modes of operation and capacitance calculation are discussed in depth. A comprehensive comparison with various nine-level topologies has been conducted in terms of total component count, total standing voltage, capacitor voltage, and approximate cost to demonstrate the proposed topology’s benefits. A 400-W inverter prototype is constructed, and the experimental findings under various operating situations are reviewed.